Composite solid electrolyte, preparation method and solid-state lithium battery containing composite solid electrolyte

By using specific contents of polymers, lithium salts and high specific surface area inorganic mesoporous fillers in composite solid electrolytes, the shortcomings of existing electrolytes in room temperature conductivity and long cycle performance are solved, and a high-efficiency and low-cost solid lithium battery is achieved.

CN119852500APending Publication Date: 2025-04-18CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311354648.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing composite solid electrolytes have shortcomings in room temperature ionic conductivity and long cycle performance, and the high density and high cost of inorganic particles limit the energy density and cost-effectiveness of solid-state batteries.

Method used

Composite solid electrolytes using specific contents of polymers, lithium salts and inorganic mesoporous fillers, where the inorganic mesoporous fillers have small pore sizes and high specific surface area, which can effectively improve conductivity and improve cycle stability.

Benefits of technology

High ionic conductivity and excellent long cycle performance are achieved, reducing the cost of solid-state batteries, and improving energy density and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852500A_ABST
    Figure CN119852500A_ABST
Patent Text Reader

Abstract

The invention relates to a composite solid electrolyte, a preparation method and a solid-state lithium battery containing the composite solid electrolyte, and the composite solid electrolyte comprises 35-42 wt% of a polymer, 53-64 wt% of a lithium salt and 1-5 wt% of an inorganic mesoporous filler based on the weight of the composite solid electrolyte; the molar ratio of silicon to aluminum of the inorganic mesoporous filler is (0-85): 1, the average pore size is 2-10nm, and the specific surface area is more than 500m < 2 > / g. When the composite solid electrolyte disclosed by the invention is applied to the solid-state lithium battery, the composite solid electrolyte has relatively high ionic conductivity and excellent long cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of new energy materials, and in particular, to a composite solid electrolyte and a preparation method thereof, and a solid-state lithium battery comprising the electrolyte. Background Art

[0002] Currently, most commercial lithium-ion batteries use flammable organic electrolytes, which have great limitations in improving battery energy density and safety. Therefore, solid electrolytes, as the key to solid-state lithium batteries, have received extensive attention and research.

[0003] Polymer solid electrolytes have the advantages of light weight, low price, easy processing, and good flexibility, but their room temperature ionic conductivity is low and their mechanical lightness is low; inorganic solid electrolytes have high room temperature ionic conductivity, high ion migration number, good mechanical properties and thermal stability, but their interface contact with the electrode is poor. Through the "rigid and flexible" design strategy, the flexible polymer matrix and the rigid inorganic filler are compounded, and the synergistic effect of the two is utilized to prepare a composite solid electrolyte. This type of electrolyte has high ionic conductivity, high mechanical strength and good interface contact, which is suitable for large-scale processing and application in solid-state batteries. However, inorganic particles with non-porous structures are often used as fillers for composite solid electrolytes. The specific surface area of ​​such inorganic particles is small, and the reduction of polymer crystallinity is not obvious, and the room temperature ionic conductivity of the electrolyte cannot be significantly improved; at the same time, the density and cost of such inorganic particles are high, which limits the improvement of energy density and cost reduction of solid-state batteries. Professor Cao Peng's team combined high-conductivity garnet-type Li 6.5 La 3 Zr 1.5 Ta 0.1 Nb 0.4 O 12 (LLZTNO) powder was embedded in polyvinylidene fluoride (PVDF) matrix to prepare a composite electrolyte, but the room temperature ionic conductivity of the composite electrolyte was only 1.05×10 -4 Scm -1 The lithium symmetric battery assembled with the composite electrolyte has a high -1 A short circuit occurred after only 400 cycles at a current density of .

[0004] In addition, composite solid electrolytes often have trace amounts of residual solvents. An appropriate amount of residual solvent can improve ionic conductivity, but an excessive amount of residual solvent will cause serious side reactions with electrode materials, affecting the cycle stability of solid-state batteries. The research group of Academician Zhang Liqun of Beijing University of Chemical Technology studied the effect of residual solvents on the lithium stability of composite solid electrolytes and found that residual DMF solvent in PEO-LLZTO and PVDF-LLZTO composite solid electrolytes will reduce the lithium stability of the electrolyte. Summary of the invention

[0005] The purpose of the present disclosure is to provide a composite solid electrolyte and a preparation method thereof, and a solid-state lithium battery comprising the electrolyte. When the composite solid electrolyte is applied to a solid-state lithium battery, it has high ionic conductivity and excellent long cycle performance.

[0006] In order to achieve the above-mentioned object, the first aspect of the present disclosure provides a composite solid electrolyte, which comprises 35-42 wt% of a polymer, 53-64 wt% of a lithium salt and 1-5 wt% of an inorganic mesoporous filler, based on the weight of the composite solid electrolyte;

[0007] The inorganic mesoporous filler has a silicon-aluminum molar ratio of 0 to 85:1, an average pore diameter of 2 to 10 nm, and a specific surface area of ​​500 m 2 / g or above.

[0008] Optionally, based on the weight of the composite solid electrolyte, the composite solid electrolyte includes 38-40 wt% of a polymer, 56-60 wt% of a lithium salt and 2-4 wt% of an inorganic mesoporous filler; the inorganic mesoporous filler has a silicon-aluminum molar ratio of 25-85:1, an average pore size of 2-5 nm, and a specific surface area of ​​800 m 2 / g or above.

[0009] Optionally, the polymer includes a first polymer and a second polymer; the first polymer is a polyvinylidene fluoride based copolymer, and the polyvinylidene fluoride based copolymer is selected from one or more of polyvinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymer and polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene copolymer, preferably polyvinylidene fluoride-hexafluoropropylene;

[0010] The second polymer is a polycarbonate polymer; the second polymer is selected from one or more of polypropylene carbonate, polyethylene carbonate, polycyclopropylene carbonate and polyvinylene carbonate, preferably polypropylene carbonate;

[0011] The lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium perchlorate and lithium hexafluorophosphate; preferably lithium bis(trifluoromethanesulfonyl imide).

[0012] Optionally, in the polymer, the mass ratio of the first polymer to the second polymer is 1:0.1-0.25, preferably 1:0.15-0.2.

[0013] Optionally, the inorganic mesoporous filler is selected from one or more of mesoporous molecular sieves, mesoporous silica aerogels and mesoporous ZIF-8; preferably mesoporous molecular sieves; the total pore volume of the mesoporous molecular sieve is 0.8 to 1 cm3 / g; further selected from one or more of mesoporous molecular sieve MCM-41, mesoporous molecular sieve SBA-15 and mesoporous molecular sieve MCM-48; preferably mesoporous molecular sieve MCM-41.

[0014] A second aspect of the present disclosure provides a method for preparing the composite solid electrolyte according to the first aspect of the present disclosure, the method comprising the following steps:

[0015] (1) first mixing a polymer, a lithium salt and an organic solvent to obtain a polymer electrolyte slurry;

[0016] (2) The inorganic mesoporous filler is mixed with the polymer electrolyte slurry in step (1) to obtain a composite electrolyte slurry.

[0017] Optionally, the organic solvent is selected from one of N,N-dimethylformamide, N-methylpyrrolidone and tetrahydrofuran; preferably N,N-dimethylformamide.

[0018] Optionally, the first mixing conditions include a temperature of 40 to 80° C., preferably 50 to 70° C.; a time of 8 to 15 hours, preferably 10 to 14 hours;

[0019] The conditions for the second mixing include: a temperature of 40 to 80° C., preferably 50 to 70° C.; a time of 8 to 15 hours, preferably 10 to 14 hours; and the second mixing is performed under ultrasonic conditions.

[0020] A third aspect of the present disclosure provides a solid-state lithium battery, the solid-state lithium battery comprising a composite solid electrolyte membrane, the composite solid electrolyte membrane comprising the composite solid electrolyte described in the first aspect of the present disclosure.

[0021] Optionally, the thickness of the composite solid electrolyte membrane is 170-180 μm; the lithium ion conductivity at 25° C. is 6×10 -4 S / cm or more.

[0022] Through the above technical scheme, the composite solid electrolyte disclosed in the present invention includes a specific content of polymer, lithium salt and inorganic mesoporous filler; the inorganic mesoporous filler has the characteristics of small pore size and large specific surface area. The composite solid electrolyte disclosed in the present invention includes an inorganic mesoporous filler with a specific structure, and has high ionic conductivity and excellent long cycle performance when applied to solid-state lithium batteries.

[0023] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0025] Figure 1 1 is a transmission electron microscope (TEM) image of the MCM-41 mesoporous molecular sieve used in the embodiments and comparative examples of the present disclosure.

[0026] Figure 2 It is the infrared spectrum of MCM-41 mesoporous molecular sieve used in the examples and comparative examples of the present disclosure.

[0027] Figure 3 is an optical photograph of the composite solid electrolyte membrane described in Example 1 of the present disclosure.

[0028] Figure 4 is a scanning electron microscope (SEM) image of the composite solid electrolyte membrane described in Example 1 of the present disclosure.

[0029] Figure 5 It is an energy spectrum (EDS) diagram of the composite solid electrolyte described in Example 1 of the present disclosure.

[0030] Figure 6 It is an electrochemical impedance spectroscopy (EIS) graph of the composite solid electrolyte described in Example 1 of the present disclosure.

[0031] Figure 7 3 is a linear sweep voltammetry (LSV) graph of the composite solid electrolyte described in Example 1 of the present disclosure.

[0032] Figure 8 It is a lithium symmetric battery cycle curve diagram of the composite solid electrolyte described in Example 1 of the present disclosure.

[0033] Fig. 9 It is a cycle curve diagram of the battery assembled with the composite solid electrolyte described in Example 1 of the present disclosure.

[0034] Fig.10 is an EIS graph of the composite solid electrolyte described in Example 2 of the present disclosure.

[0035] Fig.11 is an EIS graph of the composite solid electrolyte described in Example 3 of the present disclosure.

[0036] Fig.12 is an EIS graph of the composite solid electrolyte described in Example 4 of the present disclosure.

[0037] Fig.13 is an EIS graph of the composite solid electrolyte described in Comparative Example 1 of the present disclosure.

[0038] Fig.14is an EIS graph of the composite solid electrolyte described in Comparative Example 2 of the present disclosure.

[0039] Fig.15 is the EIS graph of the polymer solid electrolyte described in Comparative Example 3 of the present disclosure.

[0040] Fig.16 is the LSV diagram of the polymer solid electrolyte described in Comparative Example 3 of the present disclosure.

[0041] Fig.17 It is a lithium symmetric battery cycle curve diagram of the polymer solid electrolyte described in Comparative Example 3 of the present disclosure. DETAILED DESCRIPTION

[0042] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0043] The first aspect of the present disclosure provides a composite solid electrolyte, which comprises 35-42 wt% of a polymer, 53-64 wt% of a lithium salt and 1-5 wt% of an inorganic mesoporous filler, based on the weight of the composite solid electrolyte;

[0044] The inorganic mesoporous filler has a silicon-aluminum molar ratio of 0 to 85:1, an average pore diameter of 2 to 10 nm, and a specific surface area of ​​500 m 2 / g or above.

[0045] The composite solid electrolyte disclosed in the present invention includes an inorganic mesoporous filler, which has a high specific surface area, high porosity and mesoporous structure, can fully contact with the polymer matrix, reduce the crystallinity of the polymer, and improve the ionic conductivity of the composite solid electrolyte; in addition, the inorganic mesoporous filler has Lewis acid sites, which adsorb anions through Lewis acid-base action, promote the dissociation of lithium salts, increase the concentration of free lithium ions, and thus improve the ionic conductivity; and the inorganic mesoporous filler has an adsorption effect on the residual solvent in the electrolyte, which can avoid the side reaction of the residual solvent with lithium metal, and at the same time can induce the formation of an ideal inorganic-rich SEI layer, which provides long-term protection for the metal lithium negative electrode and improves its long cycle performance; the inorganic mesoporous filler has the advantages of low density, low cost and good flame retardant properties, further improving the energy density of solid-state batteries, reducing the cost of solid-state batteries and improving the safety of solid-state batteries.

[0046] According to one embodiment of the present disclosure, based on the weight of the composite solid electrolyte, the composite solid electrolyte includes 38-40 wt% of a polymer, 56-60 wt% of a lithium salt and 2-4 wt% of an inorganic mesoporous filler; the inorganic mesoporous filler has a silicon-aluminum molar ratio of 25-85:1, an average pore size of 2-5 nm, and a specific surface area of ​​800 m 2 / g or above.

[0047] According to one embodiment of the present disclosure, the polymer includes a first polymer and a second polymer; the first polymer is a polyvinylidene fluoride based copolymer, and the polyvinylidene fluoride based copolymer is selected from one or more of polyvinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymer and polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene copolymer, preferably polyvinylidene fluoride-hexafluoropropylene copolymer; the second polymer is a polycarbonate polymer; the second polymer is selected from one or more of polypropylene carbonate, polyvinyl carbonate, polycyclopropylene carbonate and polyvinylene carbonate, preferably polypropylene carbonate; the lithium salt is selected from one or more of bistrifluoromethanesulfonyl imide lithium, bisfluorosulfonyl imide lithium, bisoxalate borate lithium, difluorooxalate borate lithium, lithium perchlorate and lithium hexafluorophosphate; preferably bistrifluoromethanesulfonyl imide lithium. The above preferred embodiment is conducive to improving the ionic conductivity of the composite solid electrolyte and further improving the electrochemical performance of the lithium battery.

[0048] According to an embodiment of the present disclosure, the mass ratio of the first polymer to the second polymer is 1:0.1 to 0.25, preferably 1:0.15 to 0.2. The above embodiment is conducive to improving the ionic conductivity of the composite solid electrolyte and further improving the electrochemical performance of the lithium battery.

[0049] According to one embodiment of the present disclosure, the inorganic mesoporous filler is selected from one or more of mesoporous molecular sieves, mesoporous silica aerogels and mesoporous ZIF-8; preferably mesoporous molecular sieves; the total pore volume of the mesoporous molecular sieve is 0.8 to 1 cm 3 / g; further selected from one or more of mesoporous molecular sieve MCM-41, mesoporous molecular sieve SBA-15 and mesoporous molecular sieve MCM-48; preferably mesoporous molecular sieve MCM-41. The above preferred embodiment is conducive to improving the ionic conductivity of the composite solid electrolyte and further improving the electrochemical performance of the lithium battery.

[0050] A second aspect of the present disclosure provides a method for preparing the composite solid electrolyte according to the first aspect of the present disclosure, the method comprising the following steps:

[0051] (1) first mixing a polymer, a lithium salt and an organic solvent to obtain a polymer electrolyte slurry;

[0052] (2) The inorganic mesoporous filler is mixed with the polymer electrolyte slurry in step (1) to obtain a composite electrolyte slurry.

[0053] According to one embodiment of the present disclosure, the organic solvent is selected from one of N,N-dimethylformamide, N-methylpyrrolidone and tetrahydrofuran; preferably N,N-dimethylformamide.

[0054] According to one embodiment of the present disclosure, the conditions for the first mixing include a temperature of 40 to 80°C, preferably 50 to 70°C; a time of 8 to 15 hours, preferably 10 to 14 hours; the conditions for the second mixing include a temperature of 40 to 80°C, preferably 50 to 70°C; a time of 8 to 15 hours, preferably 10 to 14 hours; the second mixing is carried out under ultrasonic conditions.

[0055] A third aspect of the present disclosure provides a solid-state lithium battery, the solid-state lithium battery comprising a composite solid electrolyte membrane, the composite solid electrolyte membrane comprising the composite solid electrolyte described in the first aspect of the present disclosure.

[0056] According to one embodiment of the present disclosure, the method for preparing the composite solid electrolyte membrane includes coating the composite solid electrolyte slurry onto a substrate and performing a drying treatment; the conditions for the drying treatment include: a temperature of 50 to 100°C, preferably 60 to 90°C; a time of 12 to 36 hours, preferably 18 to 32 hours; and the drying treatment is performed under vacuum conditions.

[0057] According to one embodiment of the present disclosure, the thickness of the composite solid electrolyte membrane is 170-180 μm; the lithium ion conductivity at 25°C is 6×10 -4 S / cm or more.

[0058] Unless otherwise specified, the raw materials used in the following examples and comparative examples were obtained from commercial sources.

[0059] The mesoporous molecular sieve used in the present disclosure is MCM-41, whose silicon to aluminum ratio (SiO 2 / Al 2 O 3 The molar ratio is 25:1, the average pore size is about 3.5nm, and the specific surface area is 850m 2 / g, total pore volume is 0.8~1cm 3 / g, its pore structure is as follows Figure 1 As shown, it is a typical hexagonal ordered pore structure; its infrared spectrum is as follows Figure 2 As shown, at 1095cm -1 The strong absorption peak is attributed to the antisymmetric stretching vibration of Si-O-Si bond.

[0060] During ultrasonic cleaning, a KQ-300DE numerically controlled ultrasonic cleaner was used with a power of 80%.

[0061] Ionic conductivity test: The impedance of the composite electrolyte was measured using AC impedance technology, the test temperature was 25°C, and the test frequency was 0.01 to 10 6 Hz, the test instrument used is Metrohm Autolab (PGSTAT302N). Stainless steel is used as the blocking electrode during the test, the composite solid electrolyte membrane is sandwiched between two stainless steel sheets, and a stainless steel / composite electrolyte / stainless steel button cell is assembled. According to the thickness of the composite solid electrolyte membrane (L), the area of ​​the stainless steel sheet (S) and the impedance of the composite solid electrolyte (R), the ionic conductivity of the electrolyte membrane is calculated by the formula σ=L / (S*R).

[0062] Electrochemical stability window test: Linear sweep voltammetry (LSV) was used for testing with a scan rate of 0.5 mVs -1 , the scanning range is 1.5~6V(vs.Li + / Li), and the test instrument used was Shanghai Chenhua CHI660c electrochemical workstation. During the test, the composite electrolyte was sandwiched between the stainless steel sheet and the metal lithium sheet to assemble the stainless steel / composite electrolyte / lithium button cell.

[0063] Lithium metal stability test: Constant current charge and discharge test was used to evaluate the lithium stability of the composite solid electrolyte. The test instrument used was Land CT2001A and the test temperature was 30°C. Before the test, the composite electrolyte was sandwiched between two lithium metal sheets to assemble a lithium / composite electrolyte / lithium symmetrical battery.

[0064] Battery performance test: 2 O<0.1ppm,O 2 The NCM811 / composite electrolyte / lithium battery was assembled in an argon glove box with a concentration of <0.1ppm and the charge and discharge test was performed using Land CT2001A with a voltage range of 2.7 to 4.3V and a temperature of 30°C (1C = 200mAg -1 ).

[0065] SEM and EDS were tested on a Hitachi Regulus 8230 scanning electron microscope and its matching energy dispersive spectrometer.

[0066] Example 1

[0067] (1) In H 2 O<0.1ppm,O 2In an argon glove box with a concentration of <0.1ppm, 0.5g of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), 0.1g of polypropylene carbonate (PPC), and 0.9g of lithium bistrifluoromethanesulfonyl imide (LiTFSI) were weighed and added into 6ml of DMF, dissolved at 60°C for 1 hour, and then stirred continuously for 12 hours to obtain a polymer electrolyte slurry; wherein the mass ratio of the first polymer to the second polymer was 1:0.2;

[0068] (2) 0.0306 g of mesoporous MCM-41 (2% of the total mass of the composite electrolyte) was mixed with the polymer electrolyte slurry obtained in step (1), and ultrasonically treated at 60° C. for 1 hour, and then continuously stirred for 12 hours to obtain a composite electrolyte slurry;

[0069] (3) The composite electrolyte slurry was placed on a polytetrafluoroethylene plate and coated with a doctor blade. After vacuum drying at 70° C. for 24 hours, the composite solid electrolyte membrane was peeled off from the polytetrafluoroethylene plate to obtain a composite solid electrolyte membrane. The composite electrolyte membrane was cut into discs with a diameter of 19 mm and used for performance testing.

[0070] The optical photograph of the composite solid electrolyte membrane obtained in Example 1 is as follows: Figure 3 As shown, the composite solid electrolyte membrane obtained in Example 1 was subjected to SEM and EDS tests. The SEM of the composite solid electrolyte membrane is as follows: Figure 4 As shown, the EDS diagram is Figure 5 As shown, the SEM image shows that there are a large number of micropores on the surface of the composite electrolyte membrane and the pores are evenly distributed. The EDS image shows that the MCM-41 mesoporous molecular sieve filler is evenly distributed in the composite solid electrolyte membrane.

[0071] Example 2

[0072] (1) In H 2 O<0.1ppm,O 2 In an argon glove box with a concentration of <0.1ppm, 0.5g PVDF-HFP, 0.1g PPC, and 0.9g LiTFSI were weighed and added into 6ml DMF, dissolved at 60°C for 1 hour, and then stirred continuously for 12 hours to obtain a polymer electrolyte slurry; wherein the mass ratio of the first polymer to the second polymer was 1:0.2;

[0073] (2) 0.0625 g of mesoporous MCM-41 (4% of the total mass of the composite electrolyte) was mixed with the polymer electrolyte slurry obtained in step (1), and ultrasonically treated at 60° C. for 1 hour, and then continuously stirred for 12 hours to obtain a composite electrolyte slurry;

[0074] (3) The composite electrolyte slurry was placed on a polytetrafluoroethylene plate and coated with a doctor blade. After vacuum drying at 70° C. for 24 hours, the composite solid electrolyte membrane was peeled off from the polytetrafluoroethylene plate to obtain a composite solid electrolyte membrane. The composite electrolyte membrane was cut into discs with a diameter of 19 mm and used for performance testing.

[0075] Example 3

[0076] The method of this embodiment 3 is the same as that of embodiment 1, except that in step (1), 0.4 g PVDF-HFP and 0.2 g PPC are weighed, wherein the mass ratio of the first polymer to the second polymer is 1:0.5.

[0077] Example 4

[0078] The method of Example 4 is the same as that of Example 1, except that 0.6 g of PVDF-HFP is weighed in step (1).

[0079] Comparative Example 1

[0080] (1) In H 2 O<0.1ppm,O 2 In an argon glove box with a concentration of <0.1ppm, 0.5g PVDF-HFP, 0.1g PPC, and 0.9g LiTFSI were weighed and added into 6ml DMF, dissolved at 60°C for 1 hour, and then stirred continuously for 12 hours to obtain a polymer electrolyte slurry; wherein the mass ratio of the first polymer to the second polymer was 1:0.2;

[0081] (2) 0.0958 g of mesoporous MCM-41 (6% of the total mass of the composite electrolyte) was mixed with the polymer electrolyte slurry obtained in step (1), and the mixture was ultrasonically treated at 60° C. for 1 hour and then continuously stirred for 12 hours to obtain a composite electrolyte slurry;

[0082] (3) The composite electrolyte slurry was placed on a polytetrafluoroethylene plate and coated with a doctor blade. After vacuum drying at 70° C. for 24 hours, the composite solid electrolyte membrane was peeled off from the polytetrafluoroethylene plate to obtain a composite solid electrolyte membrane. The composite electrolyte membrane was cut into discs with a diameter of 19 mm and used for performance testing.

[0083] Comparative Example 2

[0084] (1) In H 2 O<0.1ppm,O 2 In an argon glove box with a concentration of <0.1ppm, 0.5g PVDF-HFP, 0.1g PPC, and 0.9g LiTFSI were weighed and added into 6ml DMF, dissolved at 60°C for 1 hour, and then stirred continuously for 12 hours to obtain a polymer electrolyte slurry; wherein the mass ratio of the first polymer to the second polymer was 1:0.2;

[0085] (2) 0.1304 g of mesoporous MCM-41 (8% of the total mass of the composite electrolyte) was mixed with the polymer electrolyte slurry obtained in step (1), and the mixture was ultrasonically treated at 60° C. for 1 hour and then continuously stirred for 12 hours to obtain a composite electrolyte slurry;

[0086] (3) The composite electrolyte slurry was placed on a polytetrafluoroethylene plate and coated with a doctor blade. After vacuum drying at 70° C. for 24 hours, the composite solid electrolyte membrane was peeled off from the polytetrafluoroethylene plate to obtain a composite solid electrolyte membrane. The composite electrolyte membrane was cut into discs with a diameter of 19 mm and used for performance testing.

[0087] Comparative Example 3

[0088] (1) In H 2 O<0.1ppm,O 2 In an argon glove box with a concentration of <0.1ppm, 0.5g PVDF-HFP, 0.1g PPC, and 0.9g LiTFSI were weighed and added into 6ml DMF, dissolved at 60°C for 1 hour, and then stirred continuously for 24 hours to obtain a polymer electrolyte slurry; wherein the mass ratio of the first polymer to the second polymer was 1:0.2;

[0089] (2) The polymer electrolyte slurry was placed on a polytetrafluoroethylene plate and coated with a doctor blade. After vacuum drying at 70° C. for 24 hours, the polymer solid electrolyte membrane was peeled off from the polytetrafluoroethylene plate to obtain a polymer solid electrolyte membrane. The polymer solid electrolyte membrane was cut into discs with a diameter of 19 mm and used for performance testing.

[0090] Test Example 1

[0091] Impedance tests were performed on the composite solid electrolytes of Examples 1 to 4 and Comparative Examples 1 to 3, and the ionic conductivity at 25° C. was calculated. Meanwhile, electrochemical stability window tests were performed on the composite solid electrolytes of Example 1 and Comparative Example 3. The results are shown in Table 1.

[0092] Table 1

[0093]

[0094]

[0095] According to the results in Table 1, the composite solid electrolyte and composite solid electrolyte membrane of the present invention have higher ionic conductivity. By comparing Example 1 with Comparative Example 3, it can be seen that the composite solid electrolyte of the present invention also has a higher oxidation resistance potential, indicating that the composite solid electrolyte membrane can meet the use of positive electrode materials under high pressure. By comparing Example 1 with Example 3, it can be seen that within the mass ratio range of the first polymer and the second polymer of the present invention, the ionic conductivity of the obtained composite solid electrolyte is higher. By comparing Example 1 with Example 4, it can be seen that when the polymer of the present invention includes the first polymer and the second polymer, the ionic conductivity of the obtained composite solid electrolyte is higher.

[0096] Test Example 2

[0097] The composite solid electrolyte / solid electrolyte obtained in Example 1 and Comparative Example 3 was assembled into a lithium symmetric battery, and the electrochemical performance was tested. The cycle curve of the lithium symmetric battery assembled with the composite solid electrolyte in Example 1 is as follows: Figure 8 As shown in the figure, it can be seen that at 0.1 mA cm -2 Under the current density, the symmetrical battery can stably cycle 1000 times, and its overpotential is 16mV, which shows that the composite solid electrolyte of the present invention has good interfacial compatibility and stability with the metal lithium electrode; the charge and discharge curves of the NCM811 / composite electrolyte / lithium battery assembled by the composite solid electrolyte described in Example 1 are as follows: Fig. 9 As shown in the figure, it can be seen that the composite solid electrolyte exhibits excellent electrochemical performance at 30°C and 0.5C, and the discharge capacity of the first cycle is 162.7 mAh g at an operating voltage of 2.7V to 4.3V. -1 After 100 cycles, the discharge capacity is 149.5 mAh g -1 , the capacity retention rate reached 91.9% and the average Coulomb efficiency was as high as 97.3%.

[0098] The cycle curve of the lithium symmetric battery assembled with the polymer solid electrolyte described in Comparative Example 3 is as follows Fig.17 As shown in the figure, it can be seen that at 0.1mAcm -2 Under the current density, the symmetrical battery short-circuited after being stably cycled for about 300 cycles, and its cycle stability was lower than that of Example 1.

[0099] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0100] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0101] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A composite solid electrolyte, characterized in that: Based on the weight of the composite solid electrolyte, the composite solid electrolyte includes 35-42 wt% of a polymer, 53-64 wt% of a lithium salt and 1-5 wt% of an inorganic mesoporous filler; The inorganic mesoporous filler has a silicon-aluminum molar ratio of 0 to 85:1, an average pore diameter of 2 to 10 nm, and a specific surface area of ​​500 m 2 / g or above.

2. The composite solid electrolyte according to claim 1, wherein Based on the weight of the composite solid electrolyte, the composite solid electrolyte includes 38-40 wt% of a polymer, 56-60 wt% of a lithium salt and 2-4 wt% of an inorganic mesoporous filler; The inorganic mesoporous filler has a silicon-aluminum molar ratio of 25 to 85:1, an average pore size of 2 to 5 nm, and a specific surface area of ​​800 m 2 / g or above.

3. The composite solid electrolyte according to claim 1, wherein The polymer comprises a first polymer and a second polymer; the first polymer is a polyvinylidene fluoride vinyl copolymer, and the polyvinylidene fluoride vinyl copolymer is selected from one or more of a polyvinylidene fluoride-hexafluoropropylene copolymer, a polytetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymer and a polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene copolymer, preferably a polyvinylidene fluoride-hexafluoropropylene copolymer; The second polymer is a polycarbonate polymer; the second polymer is selected from one or more of polypropylene carbonate, polyethylene carbonate, polycyclopropylene carbonate and polyvinylene carbonate, preferably polypropylene carbonate; The lithium salt is selected from one or more of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium perchlorate and lithium hexafluorophosphate; preferably lithium bis(trifluoromethanesulfonyl imide).

4. The composite solid electrolyte according to claim 3, wherein In the polymer, the mass ratio of the first polymer to the second polymer is 1:0.1 to 0.25, preferably 1:0.15 to 0.

2.

5. The composite solid electrolyte according to claim 1, wherein The inorganic mesoporous filler is selected from one or more of mesoporous molecular sieves, mesoporous silica aerogels and mesoporous ZIF-8; preferably mesoporous molecular sieves; the total pore volume of the mesoporous molecular sieve is 0.8 to 1 cm 3 / g; further selected from one or more of mesoporous molecular sieve MCM-41, mesoporous molecular sieve SBA-15 and mesoporous molecular sieve MCM-48; preferably mesoporous molecular sieve MCM-41.

6. A method for preparing the composite solid electrolyte according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: (1) first mixing a polymer, a lithium salt and an organic solvent to obtain a polymer electrolyte slurry; (2) The inorganic mesoporous filler is mixed with the polymer electrolyte slurry in step (1) to obtain a composite electrolyte slurry.

7. The method according to claim 6, wherein: The organic solvent is selected from one of N,N-dimethylformamide, N-methylpyrrolidone and tetrahydrofuran, preferably N,N-dimethylformamide.

8. The method according to claim 6, wherein: The first mixing conditions include a temperature of 40 to 80°C, preferably 50 to 70°C; a time of 8 to 15 hours, preferably 10 to 14 hours; The conditions for the second mixing include: a temperature of 40 to 80° C., preferably 50 to 70° C.; a time of 8 to 15 hours, preferably 10 to 14 hours; and the second mixing is performed under ultrasonic conditions.

9. A solid-state lithium battery, characterized in that: The solid-state lithium battery comprises a composite solid electrolyte membrane, and the composite solid electrolyte membrane comprises the composite solid electrolyte according to any one of claims 1 to 5.

10. The solid-state lithium battery according to claim 9, wherein: The thickness of the composite solid electrolyte membrane is 170-180 μm; the lithium ion conductivity at 25°C is 6×10 -4 S / cm or more.

Citation Information

Patent Citations

  • Composite solid electrolyte and preparation method thereof

    CN109786816A

  • Composite solid polymer electrolyte membrane and preparation method and application thereof

    CN111540948A

  • Polymer composite solid electrolyte, preparation method thereof and lithium ion battery

    CN116315067A

  • Polymer electrolyte membrane and method for preparing same

    US20190140319A1

  • Preparation method for mesoporous filler compounded gel polymer electrolyte

    WO2023087212A1